Battery cell with blocking device for delaying heat propagation
By using a blocking device between lithium-ion battery cells, which includes an insulating layer and heat-resistant materials, the safety hazards caused by heat propagation are solved, the heat propagation time is extended and the maximum temperature is reduced, thereby improving the safety of the battery.
Patent Information
- Application Number
- CN202580026239.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-20
- Filing Date
- 2025-04-07
- Publication Date
- 2026-11-06
AI Technical Summary
Lithium-ion battery cells are prone to heat propagation during thermal runaway, especially in high-energy-density batteries, posing a safety hazard that could lead to significant property damage and loss of life.
A barrier device (BLD) is employed, comprising an insulating layer and heat-resistant materials, to form a thermal barrier between battery cells, preventing the propagation of heat energy. The insulating layer, composed of porous ceramic paper, flame-retardant materials, and phase change materials, remains stable at high temperatures, absorbing heat and delaying heat propagation.
It significantly extends the heat transfer time, reduces the maximum temperature, improves the safety of the battery cell, reduces the risk of thermal runaway, and is suitable for high energy density batteries.
Smart Images

Figure CN123057633A_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims the benefit and priority of U.S. Provisional Patent Application No. 63 / 575,115, filed April 5, 2024, entitled “CELLS WITH INSULATION PAPERWRAPPING FOR DELAYED HEAT PROPAGATION”. This application also claims the benefit and priority of U.S. Provisional Patent Application No. 63 / 575,185, filed April 5, 2024, entitled “HIGH HEAT CAPACITY MATERIALSFOR IMPROVED SAFETY OF HIGH ENERGY DENSITY BATTERIES”. This application also claims the benefit and priority of U.S. Provisional Patent Application No. 63 / 575,200, filed April 5, 2024, entitled “SAFETY-ENHANCEMENT STATE-OF-CHARGE (SOC) REDUCTION DEVICES FOR PROPAGATION RESISTANTLITHIUM-ION BATTERIES”. Each of these disclosures is incorporated herein by reference in its entirety. Background Technology
[0003] The limitations and drawbacks of conventional battery cell materials will become apparent to those skilled in the art by comparing these methods with certain aspects of the methods and systems of this application as illustrated in the remainder of this disclosure with reference to the accompanying drawings. Summary of the Invention
[0004] A battery cell having a blocking device for delaying heat propagation, substantially as shown in at least one of the accompanying drawings and / or described in conjunction with at least one of the drawings, is set forth more fully in the claims. Attached Figure Description
[0005] Figure 1A An exemplary blocking device (BLD) on one side of a foil is shown according to various exemplary embodiments of the present disclosure.
[0006] Figure 1B Exemplary BLDs on both sides of a foil are shown according to various exemplary embodiments of the present disclosure.
[0007] Figure 2A and Figure 2B Examples of BLDs within a battery cell according to various exemplary embodiments of the present disclosure are shown.
[0008] Figures 3 to 6Examples of BLDs coupled to batteries according to various exemplary embodiments of the present disclosure are shown.
[0009] Figure 7 An exemplary heat propagation testing apparatus according to various exemplary embodiments of the present disclosure is shown.
[0010] Figure 8A and Figure 8B Experimental results showing how heat propagation can be prevented by BLD operation according to various exemplary embodiments of this disclosure are illustrated.
[0011] Figure 9 An exemplary battery management system (BMS) for managing battery operation is illustrated according to various exemplary embodiments of the present disclosure.
[0012] Figure 10 This is a flowchart of an exemplary lamination process for forming a silicon-dominant anode cell according to various exemplary embodiments of the present disclosure.
[0013] Figure 11 This is a flowchart of a direct coating process for forming silicon-dominant anode cell cells according to an exemplary embodiment of this disclosure. Detailed Implementation
[0014] Although the technology described in this article is often described as being combined with silicon cells, it is also applicable to conventional non-silicon cells and their manufacturing processes.
[0015] Heat transfer
[0016] Lithium-ion (LIB) battery cells are commonly used in power tools, e-bikes, and electric vehicles. However, these batteries can sometimes fail, with thermal runaway (TR) being one possible failure mode. TR is a chain reaction caused by a rapid rise in battery cell temperature due to gas release and uncontrolled flames, leading to cell rupture, decomposition, and even explosion. These failures can be caused by mechanical impact, foreign material infiltration, or defects in the electrical, thermal, or manufacturing processes. LIB battery cells have limited tolerance for deviations from their specified temperature and voltage / current ranges. Exceeding these parameters can lead to overcharging and increase the risk of TR. Additionally, if a battery cell is damaged by debris during an accident, it may also enter a TR state.
[0017] Thermal transfer (TP) within a single battery cell can rapidly spread to adjacent cells, especially in large packs used in electric vehicles or energy storage systems. For example, TP within a vehicle's battery pack can endanger the entire vehicle and its occupants. Safety concerns are more pronounced in battery cells with higher energy densities, such as those containing silicon or lithium metal. These cells heat up more rapidly due to their lower thermal capacity compared to traditional graphite or nickel-based cells. High-nickel cathodes such as NMC622, NMC811, NCMA, and NCA can accelerate TP by releasing oxygen, thus exacerbating the problem.
[0018] TP (transfer-induced damage) can lead to significant property damage, injury, and even loss of life. This disclosure provides enhanced safety by reducing or preventing the risks of TP at the pack level and TR (transfer-induced damage) at the cell level.
[0019] Blocking device
[0020] Figure 1A An exemplary blocking device (BLD) 11 on one side of foil 13 is shown according to various exemplary embodiments of the present disclosure. Figure 1B Exemplary BLD 11 on both sides of foil 13 according to various exemplary embodiments of the present disclosure are shown.
[0021] Foil 13 may comprise a copper, aluminum, or polyimide film. For example, the exemplary total thickness of the film is 10 μm to 300 μm, ideally 100 μm to 300 μm or 150 μm to 300 μm.
[0022] BLD 11 may include an insulating layer, which may be reinforced using materials that further improve the properties of the insulating layer and reduce the likelihood of TP (transfer-to-conversion). The insulating layer may include insulating paper, insulating film, and / or heat-resistant ceramic fibers. Examples of suitable ceramic fibers include Al2O3 (melting point 2050°C), MgO (melting point 2800°C), ZrO2 (melting point 2715°C), 3Al2O3-2SiO2 (melting point 2000°C), oxidized forms of BeO (melting point 2570°C), SiC (melting point 2200°C), TiC (melting point 3160°C), B4C (melting point 2450°C), BN carbide (melting point 2450°C), and AlN (melting point 2450°C), and nitrate forms of Si3N4 (melting point 1800°C).
[0023] Heat-resistant materials, such as ceramic fibers or ceramic powders, can provide insulation up to 1600°C. Thermally insulating ceramic layers can be composed of high-temperature resistant oxides and binders, and are thin and flexible; depending on their composition, they can withstand temperatures up to 1600°C or even greater than 1800°C.
[0024] BLD 11 is thermally stable up to 1800°C and is designed to operate effectively over a temperature range of 100°C to 300°C, with an optimal range of 100°C to 200°C. This range ensures that the insulation layer is activated before the battery cell reaches TR conditions. The primary function of the insulation layer is to prevent heat transfer to adjacent battery cells, requiring high thermal stability to maintain safety and performance. Ideally, the material has a thermal conductivity of less than 1 W / (m·K) or less than 0.5 W / (m·K).
[0025] For example, at least 50% of the insulation layer may be ceramic. The insulation layer may include porous ceramic paper. The insulation layer may be reinforced using flame-retardant materials, high heat capacity materials, and / or phase change materials (PCMs).
[0026] The insulating layer may include, for example, a porous and flexible ceramic sheet (paper) that is thermally stable up to greater than 1500°C. The thermal conductivity of the material in this example is less than or equal to 0.45 W / (m·K) over the entire temperature range from room temperature to 1200°C. Furthermore, these thermally insulating layers may be coated or impregnated with a material that actively absorbs heat through phase change (i.e., paraffin) and chemical decomposition (i.e., Mg(OH)₂). In the example configuration, the insulating paper can act as a thermal barrier, delaying the propagation of thermal energy, and the paraffin / Mg(OH)₂ mixture can act as a heat absorber, mitigating heat transfer between battery cells. Mg(OH)₂ powder can be coated onto Al or Cu foil and dried under vacuum to remove moisture. Since the Mg(OH)₂ material decomposes into MgO + H₂O at temperatures from 330°C to 380°C, the Mg(OH)₂ material undergoes an endothermic reaction, thus effectively preventing the spread of fire by absorbing heat through the decomposition reaction when the battery cell is ignited. Alternatively, functional materials with similar endothermic reactions can be used, including Al(OH)3, AlOOH, and Ca. 10 (PO4)6(OH)2.
[0027] Incorporating PCMs, such as paraffin wax, provides additional buffering by absorbing heat through an endothermic reaction. This feature enhances thermal management by combining PCMs with insulating layers and high-heat-capacity materials. The integration of PCMs helps manage the heat generated within the battery cell, improving overall safety and performance.
[0028] The table below describes examples of suitable PCMs with endothermic peaks close to / below the TR trigger temperature in high-nickel battery cells as disclosed:
[0029] Battery structure
[0030] A battery can consist of battery cells, modules (cell bundles), and packs (module bundles). This disclosure can also be used for cell-to-pack or other higher-efficiency designs that do not include modules. The focus of this disclosure is on insulating materials and their placement within the battery cells or modules to improve safety and pressure distribution.
[0031] To prevent thermal leakage (TP) in pouch-type LIB batteries, a thermal barrier can be included inside the battery cell. When a TP occurs in the first battery cell, a blocking device (BLD) can prevent the fire from spreading to adjacent battery cells.
[0032] Figure 2A and Figure 2B Examples of BLDs within a battery cell according to various exemplary embodiments of this disclosure are shown. For example... Figure 2A and Figure 2B As shown, example BLD (such as Figure 1A (As shown) is placed between the jelly roll and the outer bag shell. Figure 2A In the middle, the BLD wraps around the stack once. Figure 2B In the middle, the BLD wraps around the stack twice (i.e. more than once).
[0033] Alternative methods for incorporating BLD include using cut pieces of paper between each battery cell (i.e., no wrapping), or wrapping not only along one dimension but also folding at the top (i.e., like a gift). The insulation layer can be calendered in a roll press or otherwise extruded to control the thickness. The insulating paper can be applied elsewhere within the battery cell (as part of the packaging material—e.g., part of a bag or can) or used as a foam pad outside the bagged battery cells in the module.
[0034] Materials can be added to the insulating layer through a saturation process or a coating process. The added materials can include one or more of the following: fire extinguishing materials, flame retardant materials, phase change materials, high heat capacity materials, and materials operable to undergo an endothermic reaction. The added materials can be polydimethylsiloxane (PDMS), magnesium hydroxide (Mg(OH)2), paraffin, or other polymers. The added materials have a melting point of 100°C to 200°C. The objective of this disclosure is to minimize the reduction in energy density by adding less than 5% of the insulating layer. For example, the insulating layer can reduce the energy density by less than 20%, less than 10%, less than 5%, or less than 3%. Flame retardant materials and high heat capacity materials can be added (coated or injected) to the insulating layer (particularly porous) to improve the performance of the layer and reduce the chance of TP (potentially toxic substances).
[0035] In the battery example
[0036] Figure 3 An example BLD connected to the first example battery is shown. (Reference) Figure 3The battery shown includes a separator 103 sandwiched between an anode 101 and a cathode 105, and current collectors 107A and 107B. A load 109 coupled to the battery is also shown, illustrating an example when the battery is in discharge mode. In this disclosure, the term "battery" can be used to refer to a single electrochemical cell, multiple electrochemical cell units forming a module, and / or multiple modules forming a pack. Furthermore, Figure 3 The battery shown is a very simplified example, intended only to illustrate how a lithium-ion battery cell works.
[0037] The development of portable electronic devices and the electrification of transportation have driven the demand for high-performance electrochemical energy storage. In devices ranging from small-scale (<100 Wh) to large-scale (>10 kWh), LIBs are widely used compared to other rechargeable battery chemistry due to their advantages in energy density and cyclability.
[0038] Anode 101 and cathode 105, together with current collectors 107A and 107B, may include electrodes, which may be contained within or comprise plates or films of an electrolyte material, wherein the plates may provide a physical barrier containing the electrolyte and conductive contact with external structures. In other embodiments, the anode / cathode plates are immersed in an electrolyte, while a housing provides an electrolyte container. Anode 101 and cathode 105 are electrically coupled to current collectors 107A and 107B, which include metals or other conductive materials for providing electrical contact to the electrodes and for providing physical support for the active material during electrode formation.
[0039] Figure 3 The configuration shown illustrates a battery in discharge mode, while in a charging configuration, the load 109 can be replaced with a charger to reverse the process. For example, in one type of battery, the separator 103 is typically a thin film material made of, for example, an electrically insulating polymer, which prevents electrons from flowing from the anode 101 to the cathode 105 and vice versa, while being sufficiently porous to allow ions to pass through the separator 103. Typically, the separator 103, cathode 105, and anode 101 materials are individually formed as sheets, films, or foils coated with active materials. In this regard, different methods or processes can be used to form the electrodes, particularly the anode, which is predominantly silicon (>50% active material by capacity or weight). For example, lamination or direct coating can be used to form a silicon-containing anode (silicon anode). The sheets of cathode, separator, and anode are then stacked or rolled with the separator 103 separating the cathode 105 and anode 101 to form the battery 100. In some embodiments, the separator 103 is a sheet, and winding methods and stacking are typically used in its manufacture. In these methods, the anode, cathode, and current collector (e.g., electrode) can contain thin films.
[0040] In the example scenario, the battery may include a solid, liquid, or gel electrolyte. The separator 103 is preferably insoluble in a typical battery electrolyte, which may include, for example, compositions such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc., and dissolved LiBF4, LiAsF6, LiPF6, and LiClO4, LiFSI, LiTFSI, etc. In the example scenario, the electrolyte may contain lithium hexafluorophosphate (LiPF6) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), which can be used together in various electrolyte solvents. Lithium hexafluorophosphate (LiPF6) may be present at a concentration of about 0.1 mol (M) to 4.0 mol (M), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) may be present at a concentration of about 0 mol (M) to 4.0 mol (M). The solvent may comprise, in various percentages, one or more cyclic carbonates such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), or propylene carbonate (PC), and linear carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC). In some embodiments, the electrolyte solvent may contain one or more of EC, FEC, and / or EMC by weight, from about 0% to 40% of EC, from about 2% to 40% of FEC, and / or from about 50% to 70% of EMC.
[0041] The separator 103 can be immersed in a liquid or gel electrolyte. Furthermore, in the example embodiment, the separator 103 does not melt at temperatures below about 100°C to 140°C and exhibits sufficient mechanical properties for battery applications. During operation, the battery undergoes expansion and contraction of the anode 101 and / or the cathode 105. In the example embodiment, the separator 103 can expand and contract by at least about 5% to 10% without tearing or otherwise failing, and can also be flexible.
[0042] The membrane 103 may be sufficiently porous to allow ions to pass through once wetted by, for example, a liquid or gel electrolyte. Alternatively (or additionally), the membrane may absorb electrolytes through gelation or other processes, even without significant porosity. The membrane 103 is typically not too porous to prevent electron transfer between the anode 101 and cathode 105.
[0043] Anode 101 and cathode 105 comprise electrodes for the battery, providing electrical connection to the device for transferring charge during charging and discharging. For example, anode 101 may comprise silicon, carbon, or a combination of these materials. Typical anode electrodes comprise carbon materials and current collectors, such as copper sheets. Carbon is commonly used because of its excellent electrochemical properties and electrical conductivity. Anode electrodes currently used in rechargeable lithium-ion battery cells typically have a specific capacity of approximately 200 mAh / g. Graphite is the active material used in most lithium-ion battery anodes, with a theoretical energy density of 372 mAh / g. In contrast, silicon has a high theoretical capacity of 4200 mAh / g. To improve the volumetric and gravimetric energy densities of lithium-ion batteries, silicon can be used as the active material for cathode 105 or anode 101. Silicon anodes may exist in the form of a composite on the current collector, with >50% silicon by capacity or weight in the composite layer.
[0044] In the example scenario, anode 101 and cathode 105 store ions, such as lithium ions, used for charge separation. In this example, as... Figure 3 As shown, in discharge mode, the electrolyte carries positively charged lithium ions from the anode 101 to the cathode 105, and vice versa, through the separator 103 in charge mode. The movement of lithium ions and their reaction with the electrodes in one electrode generates free electrons, which in turn generate a charge on the opposite current collector. Current then flows from the current collector that generated the charge through the load 109 to the other current collector. The separator 103 prevents the flow of electrons inside the battery 100, allows the flow of lithium ions, and prevents direct contact between the electrodes.
[0045] When the battery discharges and provides current, the anode 101 releases lithium ions to the cathode 105 through the separator 103, generating an electron flow from one side to the other through the connected load 109. When the battery is charged, the opposite occurs, with lithium ions released from the cathode 105 and received by the anode 101.
[0046] The materials selected for the anode 101 and cathode 105 are important for reliability and the potential energy density of the battery 100. For example, to compete with internal combustion engine (ICE) technology and allow for the widespread adoption of electric vehicles (EVs), current battery batteries (LIBs) need improvements in energy, power, cost, and safety. High energy and power densities in LIBs have been achieved with the development of high-capacity and high-voltage cathodes, high-capacity anodes, and electrolytes with high voltage stability and interfacial compatibility with the electrodes. Furthermore, the use of low-toxicity materials as battery materials helps reduce process costs and promotes consumer safety.
[0047] While the performance of electrochemical electrodes depends on many factors, it largely depends on the robustness of the electrical contacts between electrode particles and between the current collector and electrode particles. The conductivity of silicon anode electrodes can be improved by adding conductive additives with different morphological properties. Carbon black (Super P), vapor-grown carbon fibers (VGCF), and mixtures of both have been pre-incorporated into the anode to improve conductivity and other properties. The synergistic interaction between the two carbon materials can facilitate electrical contact during the large volume changes of the silicon anode during charging and discharging, and provide the electrode with additional mechanical robustness and mechanical strength (e.g., holding the electrode material in place). These contact points (especially when using high aspect ratio conductive materials) promote electrical contact between the anode material and the current collector to alleviate isolation (island formation) of the electrode material, while also improving conductivity between silicon regions. Graphene and carbon nanotubes can be used because they exhibit similar advantages. Therefore, in some cases, mixtures of two or more of carbon black, vapor-grown carbon fibers, graphene, and carbon nanotubes can be used alone or in combination to obtain benefits in conductivity and other properties.
[0048] State-of-the-art lithium-ion batteries typically employ graphite-based anodes, a type of lithium-intercalation anode. However, silicon-based anodes offer improvements over graphite-dominant lithium-ion batteries. Silicon exhibits higher gravimetric capacity (4200 mAh / g vs. graphite's 372 mAh / g) and volumetric capacity (2194 mAh / L vs. graphite's 890 mAh / L). Furthermore, Si possesses a higher redox potential compared to graphite, with a voltage plateau of approximately 0.3–0.4 V vs. Li / Li+, which allows it to maintain an open-circuit potential, avoiding undesirable lithium plating and dendrite formation. While silicon exhibits excellent electrochemical activity, achieving stable cycle life for silicon-based anodes is challenging due to the large volumetric changes during lithiation and delithiation. This large volumetric change, coupled with its low conductivity, causes silicon to separate from the surrounding material in the anode, resulting in the silicon region losing electrical contact with the anode.
[0049] Furthermore, large silicon volume changes exacerbate the formation of the solid electrolyte interphase (SEI), which can further lead to electrical isolation and thus capacity loss. During charge-discharge cycling, the expansion and contraction of silicon particles cause them to pulverize, thereby increasing their specific surface area. During cycling, as the silicon surface area changes and increases, the SEI continuously decomposes and reforms. Therefore, during cycling, the SEI continuously accumulates around the pulverized silicon regions, forming a thick electronic and ionic insulating layer. This accumulated SEI increases the electrode impedance and reduces the electrode's electrochemical reactivity, which is detrimental to cycle life. Therefore, silicon anodes require a highly conductive matrix that (a) immobilizes the silicon particles within the anode, (b) is flexible enough to accommodate the large volume expansion and contraction of silicon, and (c) allows for rapid electron conduction within the matrix.
[0050] Therefore, there is a trade-off between the functions of the active material, conductive additives, and polymer binders. This balance can be adversely affected by high-energy-density silicon anodes with low conductivity and the aforementioned large volume change. The polymer binder can be pyrolyzed to produce a pyrolytic carbon matrix with embedded silicon particles. Furthermore, the polymer can be selected from polymers that are completely or partially soluble in water or other environmentally harmless solvents, or mixtures thereof, and compositions thereof. Water-insoluble polymer suspensions can also be utilized.
[0051] In some implementations, dedicated systems and / or software may be used to control and manage the battery or battery pack. In this regard, such dedicated systems may include suitable circuitry for operating and / or performing control and management-related functions or operations. Furthermore, this software may run on suitable circuitry, such as processing circuitry already present in the system (e.g., a general-purpose processing unit), or may be implemented on dedicated hardware. For example, a battery pack (e.g., a battery pack for electric vehicles) may be equipped with a battery management system (BMS) to manage the battery (or pack) and its operation.
[0052] BLD 110 (e.g., an insulating layer) can be configured in various ways, such as wrapping around the battery stack, folding on top, or placing between the jelly roll and the bag shell. These configurations offer flexible design options and can be tailored to meet specific safety and performance requirements. BLD 110 can also be used as a foam pad inside packaging materials (e.g., part of a bag or can) or outside the bag battery cells in a module. BLD 110 can also be hermetically sealed within the battery cells.
[0053] A typical battery cell without any insulating paper is approximately 4.4 mm thick. The thickness of a single insulating layer is measured to be 150 µm. By wrapping the insulating paper layer and securing the stacked cells with tape, the thickness of the battery cell stack can be measured to increase by 450 µm.
[0054] Figure 4 An example of a BLD connected to a coin cell is shown. The BLD 110 surrounds the coin cell and can be hermetically sealed into the cell.
[0055] Figure 5 An example of a BLD coupled to an electrode stack is shown. Figure 5 The process of wrapping an insulating paper layer around a battery stack is shown.
[0056] Stacks using electrodes and separators typically have electrode coatings on both sides of the current collector, except in some cases, the outermost electrode. Stacks can be formed into different shapes, such as cylindrical cell units or prismatic pouch cell units.
[0057] Figure 6 An example of a BLD connected to a cylindrical metal can battery cell is shown. The BLD 110 can be located between the separator and the outer steel can.
[0058] TP test
[0059] Figure 7 Exemplary TP testing apparatuses according to various embodiments of the present disclosure are shown.
[0060] like Figure 7 As shown, the TP testing apparatus includes a heater 701 and four pouch-shaped battery cells 703, 705, 707 and 709, located within a heat-resistant ceramic chamber 711 equipped with an infrared window 713.
[0061] During TP testing, heater 701 (e.g., a 200W heater) heats battery cell 1 703, while thermocouples 715, 717, 719, 721, and 723 measure the temperature of heater 701 and the temperature changes between battery cells 703, 705, 707, and 709. Infrared sensors, mounted through infrared window 713, provide accurate temperature and ignition time measurements. The test is conducted in a controlled environment with a ceramic chamber 711 of approximately 1 cubic foot, equipped with a tempered glass viewing window 713. Typically, four battery cells 703, 705, 707, and 709 are stacked together, with the top of one battery cell in contact with the bottom of the next. Only the bottom of the first battery cell 703 is directly on heater 701. No external barriers are placed between the battery cells. Heater 701 covers 20% of the battery cell area, and heating is controlled to achieve a heating rate exceeding 15°C / second. Thermocouple 717 between the heater and the first battery cell 703 measures the heater's heating rate to ensure it meets design specifications. Key test outputs include the time required for TP (heat transfer) and the highest temperature reached by the battery cell.
[0062] Testing of 13-layer battery cells
[0063] Figure 8A and Figure 8B Experimental results of blocking TP by BLD operation according to various exemplary embodiments of this disclosure are shown. Figure 8A It is a stack of battery cells without any BLD (Block Layout) structure, and Figure 8B It is a stack of battery cells with BLD (Block LD).
[0064] Battery cells with and without insulating paper were tested in the TP test. The thickness of the insulating layer can be adjusted according to the required insulation and the tolerance for additional thickness (additional thickness will reduce volumetric energy density).
[0065] The anode formulation used in these experiments was as follows: silicon / pyrolytic carbon / Super P = 86 / 10 / 4. The areal loading was 3.45 mg / cm². 2 LiNi was used in this experiment. 0.8 Mn 0.1 Co 0.1 O2 (NMC811) cathode (activity ratio 94%, loading 22.5 mg / cm²) 2 ).
[0066] Prior to the thermal propagation (TP) test, the battery cell was charged to 4.1V at 0.33C, with the current gradually decreasing to 0.05C. The battery cell has a capacity of 2 Ah.
[0067] Figure 8A The diagram shows the temperature versus time and voltage versus time relationships of a battery cell stack with four standard 13-layer cell cells during TP testing. Figure 8A As shown, the propagation time of the controlled battery cell (i.e., a silicon battery cell without an internal insulating layer) is approximately 35 seconds, during which the temperature typically exceeds 1300°C. The propagation time is defined as the time between the first battery cell entering the TR and the last battery cell entering the TR.
[0068] Figure 8B The temperature versus time and voltage versus time relationships of a battery stack with four 13-layer battery cells wrapped in insulating paper are shown during TP testing. In the test using insulating paper, the total propagation time from cell 1 to cell 4 increased to 685 seconds. This is an increase of approximately 20 times in propagation time. The highest temperature of the battery cells reached 1297°C. BLD significantly increased the propagation time (as expected).
[0069] This disclosure demonstrates significant improvements in delaying thermal propagation (TP) within the battery pack. Experimental results show that the use of BLD and other insulation technologies can delay heat propagation and reduce the maximum temperature by more than 400°C.
[0070] BLD combined with additional security enhancements
[0071] Additional safety features can be incorporated within the battery cell. All features can be enclosed within a battery cell housing (e.g., a can, bag, or other). Safety-enhanced BLDs can be combined with other technologies, such as non-flammable electrolytes, electrolytes with high ionic conductivity, high-temperature resistant electrolytes, heat-capacity-enhancing materials, and insulating layers.
[0072] Within a battery pack, different battery cells can incorporate different technologies, such as alternating high-heat-capacity battery cells. Overall safety design can also depend on pack components, such as heating plates or foam, which may eliminate the need for internal insulation layers or higher heat-capacity designs.
[0073] Safety features designed for high-energy-density devices may include a total energy density exceeding 600 Wh / L. The chemical composition includes silicon. The anode may be silicon-dominant. The chemical composition may include a high-nickel metal oxide containing nickel equal to or greater than that of NCM622. The battery cell may include a high-nickel (cathode) and silicon (anode). The battery cell may include a lithium metal anode.
[0074] Safety devices implemented in battery cells can be manufactured without placing significant interface materials between them (cell-to-pack design). These safety devices can reduce the volumetric or gravimetric energy density of the battery cell by <30%, ideally <20%, <10%, or <5%.
[0075] This disclosure enables high-energy-density chemistry materials such as silicon, lithium metal, and high-nickel cathodes. This disclosure allows for a simpler approach to pack creation by enclosing safety devices within the battery cells. This disclosure allows for cell-to-pack designs with no visible interfaces between battery cells, providing higher pack energy density at a lower cost. This disclosure eliminates the need for complex designs (e.g., those incorporating semiconductor temperature sensors).
[0076] Figure 9 An example battery management system (BMS) for managing battery operations is shown. For example... Figure 9 The image shows the Battery Management System (BMS) 140.
[0077] The battery management system (BMS) 140 may include components configured to manage one or more batteries (e.g., each as shown in the reference). Figure 3Suitable circuitry (e.g., processor 141) for each of the battery 100 examples. In this regard, the BMS 140 may communicate with and / or be coupled to each battery 100. In some embodiments, a separate processor (e.g., a conventional processor such as an electronic control unit (ECU), microcontroller unit (ECU), etc.), or several such separate processors, may be used and may be configured to handle algorithms or control functions relating to the battery. In these embodiments, these processors may be connected to the battery, for example via processor 141, and thus may be considered part of the BMS 140 and as part of processor 141.
[0078] In some embodiments, battery 100 and BMS 140 can communicate with and / or be connected to each other, for example, via electronic or wireless communication. In some embodiments, BMS 140 can be incorporated into battery 100. Alternatively, in some embodiments, BMS 140 and battery 100 can be combined into a common package 150. Furthermore, in some embodiments, BMS 140 and battery 100 can be separate devices / components and can only communicate with each other when they are in the same system. However, this disclosure is not limited to any particular arrangement.
[0079] Figure 10 This is an example lamination process flow diagram for forming silicon-dominant anode cell cells. The process uses a high-temperature pyrolysis process, layer removal, and lamination process on a substrate to adhere the active material layer to the current collector. This strategy can also be used with other types of anodes, such as graphite, conversion anodes (e.g., transition metal oxides, transition metal phosphides), and other alloy anodes (e.g., Sn, Sb, Al, P, etc.).
[0080] To manufacture the anode, a crude electrode active material is mixed in step 201. During mixing, the active material may be mixed with binders / resins (such as water-soluble PI (polyimide), PAI (polyamide-imide), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium alginate, phenolic resin or other water-soluble resins and mixtures thereof), solvents, rheology modifiers, surfactants, pH modifiers, and conductive additives. For example, the material may include carbon nanotubes / fibers, graphene sheets, metal polymers, metals, semiconductors, and / or metal oxides. For example, silicon powder with a particle size of 1 μm to 30 μm or 5 μm to 30 μm can be dispersed at, for example, 1000 rpm in a polyamide resin, PAI, or PI (15% to 25% solids in N-methylpyrrolidone (NMP) or deionized (DI) water), for example, for 10 minutes. Then, a conjugated carbon / solvent slurry can be added and dispersed at, for example, 2000 rpm, for example, for 10 minutes, to achieve a slurry viscosity of 2000 cP to 4000 cP and a total solids content of about 30% to 40%. The pH of the slurry can be varied from acidic to alkaline, which is beneficial for controlling the solubility, conformation, or adhesion behavior of the water-soluble polyelectrolyte (e.g., polyamide, carboxymethyl cellulose, or polyacrylic acid). Ionic or nonionic surfactants can be added to promote wetting of the slurry or insoluble components used in the coating process substrate. Particle size and mixing time can be varied to configure the electrode coating density and / or roughness.
[0081] Furthermore, the cathode electrode coating layer can be mixed in step 201 and coated (e.g., onto aluminum), wherein the electrode coating layer may comprise a cathode material mixed with the carbon precursor and additives described above for the anode electrode coating layer. The cathode material may comprise lithium nickel cobalt manganese oxide (NMC (also known as NCM):LiNi x Co y Mn z O2, x+y+z=1), lithium iron phosphate (LFP: LiFePO4 / C), lithium nickel manganese spinel (LNMO: e.g., LiNi 0.5 Mn 1.5 O4), lithium nickel cobalt aluminum oxide (NCA: LiNi a Co b Al c O2, a+b+c =1), lithium manganese oxide (LMO: e.g., LiMn2O4), quaternary systems of lithium nickel cobalt manganese aluminum oxide (NCMA: e.g., Li[Ni 0.89 Co 0.05 Mn 0.05 Al 0.01O2, lithium cobalt oxide (LCO: e.g., LiCoO2), lithium manganese iron phosphate (LMFP: e.g., LiMnxFe(1-x)PO4), and other lithium-rich cathode or similar materials, or combinations thereof. Particle size and mixing time can be varied to configure electrode coating density and / or roughness.
[0082] In step 203, the slurry can be coated onto the substrate. In this step, the slurry can be applied at, for example, 2 mg / cm³. 2 Up to 4 mg / cm 2 The load is coated onto a polyester, polyethylene terephthalate (PET), or polyester film, and then dried in step 205 to obtain an anode with a high silicon content and a residual solvent content of less than 15%. This step is followed by an optional calendering process in step 207, in which the film / substrate can be processed into a smooth and dense sheet of material using a series of hard rollers.
[0083] In step 209, the film containing the active material can then be removed from the PET, wherein the active material layer can be peeled off from the polymer substrate. Following peeling, a pyrolysis step 211 can be performed, in which the material is heated to, for example, 600 to 1250°C for 1 to 3 hours, sliced, and vacuum dried using a two-stage process (120°C for 15 hours, 220°C for 5 hours). If a polypropylene (PP) substrate is used, the peeling process can be skipped, and PP may leave approximately 2% carbon residue after pyrolysis.
[0084] In step 213, electrode material can be laminated onto the current collector. For example, a copper foil with a thickness of 5 μm to 20 μm can be laminated at, for example, 0.2 mg / cm³. 2 Up to 0.6 mg / cm 2 The nominal load is coated with polyamide-imide (coated in NMP with 6% wt% varnish and dried under vacuum, for example, at 110°C, for example, for 12 to 18 hours). The anode sheet can then be laminated onto a current collector coated with an adhesive. In an example scenario, a heated hydraulic press is used to laminate the silicon-carbon composite film onto the coated copper. Examples of lamination processes include holding the film at 300°C and 3000 to 5000 psi for 30 to 70 seconds to form the finished silicon composite electrode.
[0085] Before the formation process, the battery cell can be evaluated. Measurements may include impedance values, open-circuit voltage, electrode and cell thickness measurements. Formation cycling is defined as any type of charge / discharge within the battery cell, done to prepare for general cycling of the battery cell, and is considered part of the battery cell manufacturing process. Different charge and discharge rates can be used during the formation step. During formation, initial lithiation of the anode may be performed, followed by delithiation. The battery cell may be clamped during formation and / or cycling.
[0086] Figure 11 This is a flow chart of a direct coating process for forming a silicon-dominant anode cell according to an exemplary embodiment of the present disclosure. The process includes physically mixing active materials, conductive additives, and binders together, and directly coating the mixed slurry onto a current collector prior to pyrolysis. This example process includes a direct coating process in which an anode or cathode slurry is directly coated onto copper foil using a binder (such as CMC, SBR, PAA, sodium alginate, PAI, PI, and mixtures and combinations thereof).
[0087] In step 301, the active material can be mixed with, for example, a binder / resin (e.g., CMC / SBR, PI, PAI, or phenolic resin), a solvent (e.g., NMP, water, other environmentally friendly solvents, or mixtures thereof), and a conductive additive. For example, the material may include carbon nanotubes / fibers, graphene sheets, metal polymers, metals, semiconductors, and / or metal oxides. For example, silicon powder with a particle size of 1 μm to 30 μm can be dispersed at, for example, 1000 rpm in CMC / SBR, polyamide resin, PAI, PI (15% solids in DI water or N-methylpyrrolidone (NMP)) for, for example, 10 minutes, and then a conjugated carbon / solvent slurry can be added and dispersed at 2000 rpm for, for, for, for, for, 10 minutes, to obtain a slurry with a viscosity of 2000 cP to 4000 cP and a total solids content of about 30% to 40%.
[0088] Furthermore, the cathode active material can be mixed in step 301, wherein the active material may include lithium cobalt oxide (LCO), lithium iron phosphate, lithium nickel cobalt manganese oxide (NMC), lithium nickel cobalt aluminum oxide (NCA), lithium manganese oxide (LMO), lithium nickel manganese spinel, or similar materials or combinations thereof, mixed with the binder used for the anode active material as described above.
[0089] In step 303, the slurry can be coated onto the copper foil. In the direct coating process described herein, the anode slurry is coated onto the current collector with residual solvent, followed by drying and calendering processes to densify it. A pyrolysis step (approximately 500°C to 800°C) is then applied, causing the carbon precursor to be partially or completely converted into glassy carbon or pyrolytic carbon. Similarly, the cathode active material can be coated onto the foil material, such as aluminum. The active material layer can undergo the drying process in step 305 to reduce the residual solvent content. An optional calendering process can be used in step 307, where a series of hard rollers can be used to process the film / substrate into a smoother and denser sheet of material. In step 307, the foil and coating are optionally processed by a rolling mill for calendering, where the surface is smoothed and the thickness is controlled to be thinner and / or more uniform.
[0090] In step 309, the active material can optionally be pyrolyzed by heating to 500°C to 1000°C, causing the carbon precursor to be partially or completely converted into glassy carbon. Pyrolysis can be performed either by rolling or after stamping. If the electrode is pyrolyzed by rolling, it is then stamped into a single sheet after pyrolysis. The pyrolysis step can produce an anode active material having a silicon content greater than or equal to 50% by capacity or weight. In an example scenario, the anode active material layer may contain 20% to 95% silicon. In another example scenario, the anode active material layer may contain 50% to 95% silicon by weight. For example, if the current collecting foil is not pre-stamped / pre-drilled, the formed electrode can be perforated using a stamping roll. The stamped anode can then be used to assemble a battery cell with cathode, separator, and electrolyte materials. In some cases, a separator with significant adhesion properties can be used.
[0091] In step 313, the battery cell can be evaluated prior to the formation process. Measurements may include impedance values, open-circuit voltage, and cell and / or electrode thickness measurements. During formation, initial lithiation of the anode is performed, followed by delithiation. The battery cell can be clamped during formation and / or early cycling. Formation cycling is defined as any type of charge / discharge of the battery cell, done in preparation for general cycling of the battery cell, and is considered part of the battery cell manufacturing process. Different charge and discharge rates can be used in the formation step.
[0092] As used herein, “and / or” means any one or more items in the list connected by “and / or”. As used herein, the term “exemplary” means used as a non-limiting example, instance, or illustration. As used herein, the terms “e.g.” and “for example” set forth a list of one or more non-limiting examples, instances, or illustrations. As used herein, a circuit is “operable” to perform a function, provided it includes the hardware and code necessary to perform that function (if necessary), regardless of whether the function’s performance is disabled or not enabled (e.g., by user-configurable settings, factory adjustments, etc.). As used herein, the term “based on” means “at least partially based on”. For example, “x based on y” means that “x” is at least partially based on “y” (e.g., it may also be based on z).
[0093] Although the methods and / or systems of this disclosure have been described with reference to certain embodiments, those skilled in the art will understand that various modifications and substitutions can be made without departing from the scope of the methods and / or systems of this disclosure. Furthermore, many modifications can be made to adapt specific circumstances or materials to the teachings of this disclosure without departing from its scope. Therefore, the purpose of the methods and / or systems of this disclosure is not limited to the specific embodiments disclosed, but rather to include all embodiments falling within the scope of the appended claims.
Claims
1. A battery device, comprising: Battery cells, and An insulating layer that is airtightly sealed within the battery cell.
2. The battery device according to claim 1, wherein the insulating layer is thermally stable at temperatures up to 1800°C.
3. The battery device according to claim 1, wherein the insulating layer has a thermal conductivity of less than 1 W / (m·K).
4. The battery device according to claim 1, wherein the insulating layer comprises a ceramic material.
5. The battery device according to claim 1, wherein at least 50% of the insulating layer is ceramic.
6. The battery device according to claim 1, wherein the insulating layer comprises porous ceramic paper.
7. The battery device of claim 1, wherein the insulating layer comprises a material added by a saturation process.
8. The battery device of claim 1, wherein the insulating layer comprises a material added by a coating process.
9. The battery device of claim 1, wherein the insulating layer comprises a fire-extinguishing material.
10. The battery device of claim 1, wherein the insulating layer comprises a flame-retardant material.
11. The battery device of claim 1, wherein the insulating layer comprises polydimethylsiloxane (PDMS).
12. The battery device of claim 1, wherein the insulating layer comprises a phase change material.
13. The battery device of claim 1, wherein the insulating layer comprises a high heat capacity material.
14. The battery device according to claim 1, wherein the insulating layer comprises magnesium hydroxide (Mg(OH)2).
15. The battery device of claim 1, wherein the insulating layer comprises a material operable to undergo an endothermic reaction.
16. The battery device of claim 1, wherein the insulating layer comprises paraffin.
17. The battery device of claim 1, wherein the insulating layer comprises a polymer.
18. The battery device of claim 1, wherein the insulating layer comprises a material with a melting point above 100°C.
19. The battery device of claim 1, wherein the insulating layer comprises a material with a melting point below 200°C.
20. The battery device of claim 1, wherein the insulating layer reduces the energy density of the battery device by less than 5%.
